For You, Lili Marlene : A Memoir of World War II - Peters, Robert, 1924-2014 (Book collections on Project MUSE., 1995)
Drafted into the U.S. army in 1943, Robert Peters was a shy and devout eighteen-year-old from a remote and impoverished Wisconsin farm. Now one of our leading poets, he has written a lyrical memoir of a young man coming of age in the middle of World War II, making his way through personal land mines of morality and sexuality. In this sequel to Crunching Gravel, his celebrated account of a rural boyhood, Peters writes with humor and honesty of his self-revelations. After a moving leave-taking from his family and the wilderness farm he loves, he is thrust into army life. The close quarters of the barracks, the horseplay among the men, the bravado regarding war and women, and the unshakable military taboo against "perverts" throw him into confusion. Troubled by homosexual feelings, he struggles to get through basic training in South Carolina without earning the label "sissy." Inspired by patriotism and Hollywood war movies, he carefully practices his salute. Disillusioned by a cynical post chaplain, he abandons his plans to become a Lutheran minister. As awkward with his M1 rifle as he had been at home with a deer rifle, Peters is classified as a clerk and shipped to England. He hangs back in turmoil as London streetwalkers proposition him and older soldiers flirt with him. On leave in Paris, where he finally shares a prostitute with a friend he silently loves, he visits the Louvre and waits for hours in line to see the glamorous Marlene Dietrich. Through the war and the post-war occupation of Germany, as Peters's diligence and growing confidence result in promotion to battalion sergeant-major, the voice of Dietrich singing "Lili Marlene" stays with him, evoking love and beauty in the midst of destruction and deprivation.